Marcha sobre Pequim : a república popular da China na política externa do governo Geisel (1974-1979) segundo o jornal do Brasil e o Estado de São Paulo - Müller, Pricila Niches (2019)
The present study addresses the relation between the press and the foreign policy in Brazil with focus on the analysis of the press strategy concerning the foreign policy during the Geisel government (1974-1979), which sought the diversification of partnerships with the use of a policy called "Pragmatic, responsible and ecumenical”, with emphasis on the initial establishment of the strategic partnership with the China Popular Republic, including at the embassy level between countries. Thus, the main purpose of this study is to investigate in which way the building of a parternship between Brazil and China is portrayed in the Brazilian press in the context of the years that comprise the Geisel Government. In order to do that, newspapers were selected to analysis and the temporal cut was made for the composition of the corpus, which comprehends the year 1974 until 1979. This study was built based on the specialized bibliography and analysing texts of the main printed communication vehicles of that period: O Estado de São Paulo and Jornal do Brasil, considering that official documentation of the Brazilian government is also a guideline for newspaper research. In the course of the work, it was observed that in the 1990s the relationship between Brazil and China came to be called strategic and it was noted the need to study the origins of this partnership, examining its embryonic formation in the 1970s. Thus, the research presentes a discussion on the matter of the implications of the strategic relationship between Brazil and the Communist China during the Geisel government based on the framework elaborated by the two mentioned journals, as well as identifying the interferences that distinguish their narratives.